A method for preparing a composite membrane distillation membrane having anti-pollution and anti-wetting properties

By hydrophilic modification of the hydrophobic microporous membrane and forming a PVA/TA coating, the problems of membrane pollution and membrane wetting are solved, efficient high-salt wastewater treatment is achieved, and membrane distillation performance is improved.

CN116036887BActive Publication Date: 2025-02-28SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211662811.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-02-28
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

Hydrophobic microporous membranes are prone to membrane pollution and membrane wetting problems when dealing with complex high-salt wastewater, resulting in a decrease in permeability and a decrease in salt cutoff rate, limiting the application of membrane distillation technology.

Method used

By performing surface hydrophilic modification of the hydrophobic microporous membrane and adding tannin to the polyvinyl alcohol solution, a PVA/TA coating is formed to enhance the film's anti-oil contamination and surfactant wetting resistance.

Benefits of technology

It realizes the high permeability flux and salt cutoff rate in high-salt wastewater treatment, and has excellent anti-pollution and wetting properties, which improves the stability and efficiency of the membrane distillation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004013599320000011
    Figure HDA0004013599320000011
  • Figure HDA0004013599320000012
    Figure HDA0004013599320000012
  • Figure HDA0004013599320000021
    Figure HDA0004013599320000021
Patent Text Reader

Abstract

The invention relates to a method for preparing a pollution-resistant and wetting-resistant composite membrane distillation membrane. The invention firstly performs surface hydrophilic modification on a hydrophobic microporous membrane, then adds tannic acid into a polyvinyl alcohol solution and utilizes the solution to coat the hydrophilically modified hydrophobic microporous membrane, thereby obtaining a composite membrane distillation membrane having both oil pollution resistance and surfactant wetting resistance, thereby achieving comprehensive improvement of membrane distillation performance, ensuring high permeability flux and salt rejection rate while obtaining excellent pollution resistance and wetting resistance, having excellent treatment effect on high-salt solution containing surfactant-stabilized oil emulsion, having good structural stability and durability, being conducive to its application in actual high-salt wastewater treatment, having a wide source of raw materials, being green and environmentally friendly in process, and having low preparation cost, thereby being conducive to large-scale production and market promotion and application in the field of membrane distillation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane distillation, and in particular relates to a method for preparing a composite membrane distillation membrane that is resistant to pollution and moisture. Background Art

[0002] Membrane distillation (MD) is a desalination technology based on membrane and thermal methods. It uses a hydrophobic microporous membrane as a separation barrier and the vapor pressure difference caused by the temperature difference of the feed liquid on both sides of the membrane as the driving force for mass transfer. It pushes water vapor through the membrane and obtains ultrapure water through condensation on the permeate side, thus separating the non-volatile solutes and water in the feed liquid. Compared with advanced water treatment technologies such as reverse osmosis (RO), low-temperature multi-effect distillation (MED), and multi-stage flash distillation (MSF), membrane distillation has a low operating temperature and can utilize low-grade heat sources such as industrial waste heat, solar energy, and geothermal energy, with low energy consumption. It is insensitive to the salt concentration of the feed liquid and can break through the upper limit of the salt concentration of the RO treatment solution (70,000 mg L -1 ); separation is achieved through phase change, with a theoretical desalination rate of up to 100%; the equipment is simple and modular, with low investment cost. However, as the core of membrane distillation technology, hydrophobic microporous membranes mainly face challenges of membrane fouling and membrane wetting when treating complex high-salinity wastewater, which greatly limits the further application of membrane distillation technology.

[0003] Membrane fouling is mainly caused by organic pollutants in the feed liquid, such as proteins and oil droplets, which can adhere to the surface and pores of the hydrophobic microporous membrane through hydrophobic-hydrophobic interactions, blocking the membrane pores, thereby significantly reducing the membrane permeation flux. Membrane wetting is mainly caused by low surface energy substances or amphiphilic substances in the feed liquid, especially surfactants, which are widely present in various types of wastewater and can reduce the surface tension of the feed liquid and the liquid entry pressure (LEP) of the membrane, so that the feed liquid directly passes through the membrane pores, resulting in a significant decrease in salt rejection and process failure. Therefore, membrane fouling and membrane wetting are bottleneck problems that need to be solved urgently during the use of membrane distillation membranes.

[0004] In view of the above problems, an effective solution is to construct a hydrophilic layer on the surface of the hydrophobic microporous membrane to block the contact between pollutants and the hydrophobic membrane. However, the current methods have the following main problems: (1) The introduction of the hydrophilic layer increases the additional mass transfer resistance and reduces the permeation flux of the membrane; (2) The preparation process of the hydrophilic coating is complicated, involving high temperature, chemical cross-linking and other steps, which is not green and environmentally friendly; (3) The binding force between the hydrophilic functional layer and the hydrophobic microporous membrane is poor, and the membrane stability is poor. Therefore, it is urgent to develop a green and efficient anti-pollution coating construction method to obtain a high-performance membrane distillation membrane to ensure long-term stability in the process of high-salinity wastewater treatment. Summary of the invention

[0005] The invention aims at the deficiencies of the prior art and provides a method for preparing a composite membrane distillation membrane which is resistant to pollution and moisture.

[0006] The present invention firstly performs surface hydrophilic modification on a hydrophobic microporous membrane, then adds tannic acid into a polyvinyl alcohol solution and uses the solution to coat the hydrophilically modified hydrophobic microporous membrane, thereby obtaining a composite membrane distillation membrane that is both resistant to oil pollution and resistant to surfactant wetting, can maintain high permeation flux and salt rejection rate, and improves long-term operation stability.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a composite membrane distillation membrane that is resistant to pollution and moisture, comprising the following steps:

[0009] 1) dissolving a biomimetic adhesive and a cross-linking agent in a Tris-HCl buffer solution with a pH of 8.0-9.0 to obtain a modified solution, placing the upper surface of a hydrophobic microporous membrane in contact with the modified solution and allowing the modified solution to stand to perform surface hydrophilic modification on the hydrophobic microporous membrane, and fully washing and drying the membrane to obtain a hydrophobic microporous membrane with one side hydrophilically modified;

[0010] 2) adding polyvinyl alcohol (PVA) and tannic acid (TA) to water, stirring evenly at 90-98° C. to obtain a coating liquid;

[0011] 3) coating the coating liquid obtained in step 2) on the surface of the hydrophobic membrane modified membrane obtained in step 1) and drying it to obtain a PVA / TA layer modified composite membrane.

[0012] Preferably according to the present invention, in step 1), the biomimetic adhesive is dopamine or plant polyphenols, and the cross-linking agent is an amino-rich polymer and / or a transition metal ion.

[0013] Preferably, the biomimetic adhesive is dopamine. The plant polyphenols are prepared according to the prior art.

[0014] More preferably, the amino-rich polymer is polyethyleneimine or polyamide-amine dendrimer, and the transition metal ion is Cu 2+ or Fe 3+ .

[0015] Preferably according to the present invention, in step 1), the concentration of the biomimetic adhesive in the modified liquid is 0.5-5 mg / mL, and when the cross-linking agent is an amino-rich polymer, the mass ratio of the amino-rich polymer to the biomimetic adhesive is (0.1-5):1; when the cross-linking agent is a transition metal ion, the molar ratio of the metal ion to the biomimetic adhesive is (0.1-5):1.

[0016] Preferably according to the present invention, in step 1), the hydrophobic membrane is an intrinsically hydrophobic polymer microporous membrane.

[0017] Preferably according to the present invention, in step 1), the hydrophobic membrane is a polyvinylidene fluoride, polytetrafluoroethylene or polypropylene microfiltration membrane.

[0018] Preferably according to the present invention, in step 1), the standing time is 2 to 24 hours.

[0019] Preferably according to the present invention, in step 2), the mass percentage of polyvinyl alcohol in the coating liquid is 6% to 10%, and the mass ratio of tannic acid to polyvinyl alcohol is (1 to 4): (30-50).

[0020] Preferably according to the present invention, in step 2), the stirring time is 5 to 10 hours.

[0021] According to the preferred embodiment of the present invention, in step 2), the coating method is blade coating, drip coating, spray coating, spin coating or natural casting.

[0022] Preferably according to the present invention, in step 2), the drying method is natural air drying or oven drying at a temperature of 25 to 60° C. for a time of 0.5 to 12 h.

[0023] A composite membrane distillation membrane with anti-pollution and moisture resistance is prepared by adopting the method.

[0024] The anti-pollution and anti-wetting composite membrane distillation membrane is used for membrane distillation. When used for membrane distillation, the side coated with polyvinyl alcohol and tannic acid is in contact with the feed liquid.

[0025] According to the present invention, the feed liquid is preferably a mixed solution of water and salt to which a surfactant and / or oil are added.

[0026] After the coating liquid PVA / TA of the present invention is coated on the surface of a hydrophilically modified hydrophobic microporous membrane, after drying, the polymer network shrinks and entangles with each other, forming a stable PVA / TA coating on the membrane surface, and obtaining a composite membrane distillation membrane. Due to the high hydrophilicity of PVA and TA, the PVA / TA coating has high hydrophilicity in the air and super oleophobicity underwater, and can play an underwater anti-oil pollution role. In addition, TA, as a hydrogen bond enhancer, can further enhance the bonding between PVA polymer segments and regulate the polymer network structure. When the amount of TA added is small, the regulation of the PVA network structure is limited, and it cannot play a good anti-wetting effect; when added in excess, the strong interaction between TA and PVA makes the solution inhomogeneous, produces block aggregates, and affects the subsequent film quality. The appropriate amount of addition can make the PVA polymer network dense, play a good barrier effect on surfactants, and thus resist wetting. The high hydration of the PVA / TA coating can reduce the energy required for the evaporation of water in the feed liquid, thereby ensuring a high permeability flux in the membrane distillation process. The PVA / TA coated microporous membrane can effectively handle high-salt solutions containing surfactants and oil droplets.

[0027] The beneficial effects of the present invention are as follows:

[0028] 1. The present invention firstly performs surface hydrophilic modification on a hydrophobic microporous membrane, then adds tannic acid to a polyvinyl alcohol solution and uses the solution to coat the hydrophilically modified hydrophobic microporous membrane, thereby obtaining a composite membrane distillation membrane having both oil pollution resistance and surfactant wetting resistance. The high hydrophilicity and underwater superoleophobicity (oil contact angle>150°) of the polyvinyl alcohol / tannic acid coating enable a firm hydration layer to be formed on the membrane surface during the membrane distillation process, thereby preventing oil substances from contacting the hydrophobic membrane, thereby playing a role in resisting oil pollution.

[0029] 2. The present invention uses tannic acid as a hydrogen bond enhancer, which can further regulate the density of the polyvinyl alcohol network structure, so that the composite membrane distillation membrane can effectively resist the wetting of surfactant substances.

[0030] 3. The present invention firstly performs surface hydrophilic modification on a hydrophobic microporous membrane, and then adds tannic acid to a polyvinyl alcohol solution and uses the solution to coat the hydrophilically modified hydrophobic microporous membrane, thereby obtaining a composite membrane distillation membrane that is both resistant to oil pollution and resistant to surfactant wetting. The strong hydrogen bond interaction between the hydrophilic polyvinyl alcohol / tannic acid coating and water molecules can reduce the evaporation enthalpy of water, and some water molecules leave the evaporation interface in the form of clusters, thereby ensuring a high permeability flux in the membrane distillation process.

[0031] 4. The method of the present invention achieves a comprehensive improvement in membrane distillation performance, ensuring high permeability flux and salt rejection rate while obtaining excellent anti-pollution and anti-wetting properties. It has excellent treatment effects on high-salt solutions containing surfactant-stabilized oil emulsions, and has good structural stability and durability, which is conducive to its application in actual high-salt wastewater treatment.

[0032] 5. The present invention adopts a simple and easy coating-drying method to obtain a thin layer composite film. Compared with other methods, it does not require subsequent chemical cross-linking and high-temperature treatment processes, is more environmentally friendly, can be scaled up, has low raw material costs, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a scanning electron microscope image of the surface of the polytetrafluoroethylene microporous membrane of Example 1 of the present invention.

[0034] Figure 2 This is a scanning electron microscope image of the surface of the composite membrane distillation membrane of Example 1 of the present invention.

[0035] Figure 3 This is a scanning electron microscope image of a cross section of the composite membrane distillation membrane of Example 1 of the present invention.

[0036] Figure 4This is a scatter plot of water flux and conductivity of the composite membrane distillation membrane of Example 1 of the present invention.

[0037] Figure 5 Graph showing the underwater oil contact angle of the polyvinylidene fluoride membrane before and after modification in Example 2 of the present invention.

[0038] Figure 6 This is a scatter plot of water flux and conductivity of the composite membrane distillation membrane in Example 2 of the present invention.

[0039] Figure 7 The scatter plot is a conductivity scatter plot of the composite polytetrafluoroethylene membrane obtained by adding different amounts of tannic acid in the polyvinyl alcohol coating of the present invention.

[0040] Figure 8 The wetting conditions of the composite polytetrafluoroethylene membrane obtained by adding different amounts of tannic acid to the polyvinyl alcohol coating of the present invention are shown. DETAILED DESCRIPTION

[0041] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further description is given below in conjunction with the drawings and specific embodiments.

[0042] Example 1

[0043] A method for preparing a composite membrane distillation membrane that is resistant to pollution and moisture, comprising the following steps:

[0044] 1) 0.2 g dopamine and 0.2 g polyethyleneimine were dissolved in 100 mL Tris-HCl buffer solution (50 mM, pH = 8.5) to obtain a modified solution, and the upper surface of the polytetrafluoroethylene membrane was contacted with the modified solution. After standing for 12 hours, the membrane was cleaned and dried to obtain a polytetrafluoroethylene membrane with one side hydrophilically modified;

[0045] 2) preparing a polyvinyl alcohol / tannic acid coating solution: the mass fraction of polyvinyl alcohol is 8%, and the mass ratio of tannic acid to polyvinyl alcohol is 2:40. Specifically, 4 g of polyvinyl alcohol and 0.2 g of tannic acid are added to 45.8 g of water, heated and stirred at 95° C. for 5 h to obtain a coating solution, and cooled for standby use;

[0046] 3) Fix the membrane obtained in 1) on a glass plate, and use a scraper with a gap of 100 μm to scrape the coating liquid onto the surface of the hydrophilically modified hydrophobic membrane modified membrane, and dry it at room temperature for 3 hours to obtain a composite membrane distillation membrane, i.e., a polyvinyl alcohol / tannic acid modified polytetrafluoroethylene composite membrane, which is immersed in deionized water for use.

[0047] The unmodified polytetrafluoroethylene membrane used in this example and the obtained composite membrane distillation membrane were characterized by scanning electron microscopy.

[0048] Figure 1This is a scanning electron microscope image of the surface of a polytetrafluoroethylene microporous membrane without any modification. Figure 2 This is a scanning electron microscope image of the composite membrane distillation membrane surface. Figure 3 This is a scanning electron microscope image of the cross-section of the composite membrane distillation membrane.

[0049] pass Figures 1 to 3 It can be seen that the polytetrafluoroethylene microporous membrane presents a porous structure composed of fibers and nodules, while the surface of the composite membrane distillation membrane coating is dense and smooth. The cross-section shows that the thickness of the polyvinyl alcohol / tannic acid hydrophilic layer is about 3.7μm, and it has good structural integrity with the polytetrafluoroethylene membrane.

[0050] A solution containing 3.5% sodium chloride, 1000 ppm mineral oil and 0.1 mM surfactant sodium dodecyl sulfate was used as the feed liquid. A direct contact membrane distillation apparatus was used with the coating layer facing the feed liquid. The feed side temperature was set to 65°C and the condensation side temperature was set to 20°C. The performance of the composite membrane distillation membrane obtained in Example 1 was tested, and the conductivity and flux changes of the cold test were monitored in real time.

[0051] from Figure 4 It can be seen that the obtained composite membrane always maintains a stable permeation flux of 21.11 kg / m during the treatment process of the salt solution containing mineral oil and surfactant. -2 h -1 After 24 hours, the conductivity was still low, 1.96μScm -1 The salt rejection rate is as high as 99.99%, indicating that the composite membrane distillation membrane has excellent anti-pollution and wetting resistance. In addition, when treating a solution containing only 3.5% sodium chloride, the permeation flux of the composite membrane is almost unchanged compared with the original membrane, which is 20.34 kgm -2 h -1 and 20.06kgm -2 h -1 , the salt rejection rate was 100%, indicating that the introduction of the polyvinyl alcohol / tannic acid coating with a micron-level thickness did not cause additional mass transfer resistance, and the permeation flux and salt rejection of the modified composite membrane were maintained at a high level.

[0052] Example 2

[0053] A method for preparing a composite membrane distillation membrane that is resistant to pollution and moisture, comprising the following steps:

[0054] 1) Dissolve 0.2 g of tannic acid and 0.038 g of ferric chloride in 100 mL of Tris-HCl buffer solution (50 mM, pH = 8.8) to obtain a modified solution, contact the upper surface of the polyvinylidene fluoride membrane with the modified solution, let it stand for 6 hours, then clean and dry the membrane to obtain a polyvinylidene fluoride membrane with one side hydrophilically modified;

[0055] 2) Prepare a polyvinyl alcohol / tannic acid solution: polyvinyl alcohol mass fraction 7%, tannic acid and polyvinyl alcohol mass ratio 1:35. Specifically, add 3.5g polyvinyl alcohol and 0.1g tannic acid to 46.4g water, heat and stir at 90°C for 8h to obtain a coating solution, and cool for use.

[0056] 3) Fix the film obtained in 1) on a glass plate, use a scraper with a gap of 100 μm to scrape the coating liquid onto the film surface, dry it at 30° C. for 1 h, and obtain a polyvinyl alcohol / tannic acid modified polyvinylidene fluoride composite film, which is immersed in deionized water for use.

[0057] The underwater oil contact angle of the polyvinylidene fluoride membrane before and after modification was tested using a contact angle meter. Figure 5 As shown, the original polyvinylidene fluoride membrane without any modification exhibits oleophilic properties underwater, with an underwater oil contact angle of 39.2°, while the composite membrane distillation membrane exhibits superoleophobic properties, with an underwater oil contact angle of 155.1°.

[0058] Using a solution containing 3.5% sodium chloride and 2000ppm mineral oil as the feed solution, the anti-fouling performance of the composite membrane distillation membrane was evaluated according to the membrane performance test method in Example 1. Figure 6 .

[0059] Figure 6 The results showed that the composite membrane distillation membrane maintained a stable permeation flux of 22.42 kg / m during the treatment of salt solution containing mineral oil. -2 h -1 After 24 hours, the conductivity was still low, at 1.60 μS cm -1 , the salt rejection rate is as high as 100%, indicating that the composite membrane has excellent anti-oil pollution performance.

[0060] Example 3

[0061] A method for preparing a composite membrane distillation membrane that is resistant to pollution and moisture, comprising the following steps:

[0062] The same preparation method as described in Example 1, except that:

[0063] Step 3) Spray the solution obtained in step 2) onto the surface of the hydrophilically modified polytetrafluoroethylene membrane obtained in step 1) by spraying, with a spray gun pressure of 0.5 MPa, 10 cm vertical to the membrane surface, and a spray thickness of 10 μm. Dry at 60°C for 0.5 h to obtain a composite membrane distillation membrane, which is then immersed in deionized water for later use.

[0064] A solution containing 3.5% sodium chloride and 0.4 mM surfactant sodium dodecyl sulfate was used as the feed solution, and the membrane performance test method in Example 1 was used to evaluate the anti-wetting performance of the composite membrane distillation membrane.

[0065] The obtained composite membrane always maintained a stable permeation flux of 19.70 kg / m during the treatment process of the salt solution containing sodium dodecyl sulfate. -2 h -1 After 24 hours, the conductivity was still low, 2.14μScm -1 The salt rejection rate is as high as 99.99%, indicating that the composite membrane has excellent resistance to surfactant wetting.

[0066] Comparative Example 1

[0067] The feed solution of Example 2 was treated by the method of Example 2 using an untreated polytetrafluoroethylene membrane. The results showed that the initial permeation flux of the membrane was as low as 10 kgm -2 h -1 , and dropped to zero after 35 min. The surface polytetrafluoroethylene hydrophobic membrane suffered serious oil pollution. This is due to the underwater oleophilic characteristics of the hydrophobic membrane ( Figure 5 Left picture), so it is not suitable for treating oily high-salinity wastewater.

[0068] Comparative Example 2

[0069] The method described in Example 1 is different in that:

[0070] In step 2), 4 g of polyvinyl alcohol and 0.5 g of tannic acid were added to 45.5 g of water, and heated and stirred at 95° C. for 5 h.

[0071] The results showed that the prepared solution had a high content of tannic acid, the resulting coating liquid was uneven, and a large amount of blocky substances were generated inside. This was due to the strong interaction between tannic acid and polyvinyl alcohol, which caused the polyvinyl alcohol molecular chains to be excessively entangled and aggregated. The coating could not be used to prepare a composite film with a uniform and defect-free coating.

[0072] A solution containing 3.5% sodium chloride and 0.4 mM surfactant sodium dodecyl sulfate was used as the feed solution, and the membrane performance test method in Example 1 was used to evaluate the wetting resistance of the composite polytetrafluoroethylene membrane when the mass ratio of tannic acid to polyvinyl alcohol was 5:40.

[0073] The results show that compared with the membrane obtained in Example 1, the conductivity of the membrane increased from 1.22 μScm to -1 Increased to 20.61μScm -1 , indicating that the salt cutoff decreases and membrane wetting occurs. Figure 7 After the membrane distillation operation, the back of the membrane is photographed ( Figure 8 ) also proves the occurrence of local wetting, while the composite membrane obtained in Example 1 does not wetting. This comparative example proves that excessive addition of tannic acid reduces the anti-wetting performance of the composite membrane.

[0074] Comparative Example 3

[0075] The method described in Example 1 is different in that:

[0076] Step 2) The prepared solution does not contain tannic acid, and 4 g of polyvinyl alcohol is dissolved in 46 g of water.

[0077] A solution containing 3.5% sodium chloride and 0.4 mM surfactant sodium dodecyl sulfate was used as a feed solution, and the wetting resistance of the polyvinyl alcohol composite polytetrafluoroethylene membrane was evaluated according to the membrane performance test method in Example 1.

[0078] The results showed that the conductivity of the membrane increased from 1.29 μS cm to -1 Increased to 39.38μScm -1 , indicating that the salt cutoff decreases and membrane wetting occurs. Figure 7 After the membrane distillation operation, the back of the membrane is photographed ( Figure 8 ) also proves the occurrence of local wetting. This comparative example proves the necessity of adding tannic acid to improve the anti-wetting performance.

[0079] The above-described embodiments are preferred implementations of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a pollution-resistant and moisture-resistant composite membrane distillation membrane, characterized in that: Here are the steps: 1) dissolving a biomimetic adhesive and a cross-linking agent in a Tris-HCl buffer solution of pH=8.0-9.0 to obtain a modified solution, placing the upper surface of the hydrophobic microporous membrane in contact with the modified solution and standing for 12 hours to perform surface hydrophilic modification on the hydrophobic microporous membrane, and fully washing and drying the membrane to obtain a hydrophobic microporous membrane with one side hydrophilically modified; 2) adding polyvinyl alcohol (PVA) and tannic acid (TA) to water, stirring evenly at 95° C. to obtain a coating solution; 3) coating the coating liquid obtained in step 2) on the surface of the hydrophobic membrane modified membrane obtained in step 1) and drying to obtain a PVA / TA layer modified composite membrane; In step 1), the biomimetic adhesive is dopamine and the cross-linking agent is polyethyleneimine; The mass ratio of dopamine to polyethyleneimine is 1:1; In step 2), the mass percentage of polyvinyl alcohol in the coating liquid is 8%, and the mass ratio of tannic acid to polyvinyl alcohol is 2:40; In step 2), the stirring time is 5 hours, the coating method is scraping, the drying method is natural drying, the temperature is 25-60° C., and the time is 3 hours; In step 1), the hydrophobic membrane is a polytetrafluoroethylene membrane.

2. A pollution-resistant and moisture-resistant composite membrane distillation membrane prepared by the method described in claim 1.

3. The use of the anti-pollution and moisture-resistant composite membrane distillation membrane according to claim 2 for membrane distillation. When used for membrane distillation, the side coated with polyvinyl alcohol and tannic acid is in contact with the feed liquid.

4. The use according to claim 3, characterized in that: The feed liquid is a mixed solution of water and salt to which surfactant and / or oil are added.

Citation Information

Patent Citations

  • Preparation method for bionic construction of polyquaternary ammonium salt type antibacterial PVDF (Polyvinylidene Fluoride) membrane

    CN109200835A

  • Anti-pollution composite reverse osmosis membrane and preparation method thereof

    CN112870989A